Characterization of Productive and Reproductive Performance of Broiler Grand Parent Stock Strains (Ross, Cobb, and Hubbard) During Growing and Laying Phases - Amak Fadoli; Hamiyanti, Adelina Ari; Kamalludin, Mamat Hamidi; Nurgiartiningsih, Veronica Margareta Ani (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
Grandparent Stock (GPS) serves as the genetic cornerstone of broiler production, influencing performance at both Parent Stock and commercial levels. This study evaluated and compared the productive and reproductive traits of three major GPS broiler strains—Ross, Cobb, and Hubbard—under commercial tropical conditions in Indonesia. Data from 104,415 birds (83,102 females; 21,313 males) were collected from two national poultry companies between 2019 and 2022. Parameters included mortality, feed intake, body weight, uniformity, egg production, egg weight, and hatchability. Analysis of Variance (ANOVA) and Duncan's test were applied. Cobb showed the lowest mortality during the grower phase (0.30%) and the highest body weight uniformity (80.71%). Ross had the lowest mortality in the laying phase (0.479%) and the highest egg production (49.13%). Hubbard achieved the highest final body weight (4,727 g) and egg weight (64.85 g) but recorded the highest mortality during laying (0.870%). No significant differences were found in cumulative feed intake (132,750–134,786 g/bird) or hatchability (>94.7%) across strains. These results suggest Cobb is best for uniformity and survivability, Ross for egg productivity, and Hubbard for maximizing output, although requiring more intensive management. Strain selection should align with production priorities and local farm conditions, considering factors such as climate adaptability, resource availability, and long-term sustainability. The findings provide valuable insights for optimizing broiler breeding programs in tropical regions, enhancing genetic potential, and improving overall production efficiency.